Review and Comparative Analysis of Modern Devices For Level Gauging In Checking System And Industrial Processing Control - Nodirbek Rustambekovich Yusupbekov, Azamat Alijonovich Yusupov (International Journal of Advanced Science and Technology, 2020)
In the systems of control and management of technological processes and production are used various methods of level gauging. To ensure the safety and profitability of production processes, they must be equipped with tools that allow reliable and accurate level gauging. This is one of the key components of a tank inventory system to ensure reliable and accurate management of raw materials and storage of finished products. Currently, there are more than twenty different methods for measuring the level of liquid and bulk materials, some of which are used in industry, others have highly specialized applications. A comparative analysis of the metrological capabilities of various level gauging methods has been carried out.